Democratic Republic of Congo Country Status Report on Education : Priorities and Options for Regenerating the Education Sector - World Bank (Washington, DC, 2013)
The education system in the Democratic Republic of Congo (DRC) will play an important role in building the country's political institutions, in promoting economic growth, and in redressing inequalities. The country is emerging from a prolonged economic and political crisis which has had serious negative impacts on the education system. The main purpose of this report is to assist the DRC identify the priorities for education policy, and present options in order to assist the government in developing an education strategy. This is necessary for preparing the government's Poverty Reduction Strategy Paper and a program of assistance for the education sector by external donors. This Country Status Report is structured in six chapters covering the recent trends and current status of educational coverage, expenditures and financing at all levels of instruction in DRC, issues relating to quality in primary and secondary education, and specific issues relating to higher education. It also presents the expenditure requirements under various policy options which can be used to begin a more detailed planning for the sector. Financial simulations were undertaken for four scenarios of educational expansion in order to determine total expenditure requirements, the composition of expenditure, and the shares of different financing sources. These simulations also suggest some key policy choices which could contribute to further containing costs. The foregoing analysis suggests critical policy questions, i.e. setting goals for quantitative coverage; determining strategies for achieving the goals within each sub-sector; determining the costs of implementing the strategies; and, identifying key reforms in governance and education administration. In developing educational policy and strategy, an iterative approach will need to be adopted in order to gauge the feasibility of different options.